PROPER BREATHING IMPORTANCE IN CLASSICAL AND MODERN DANCE TRAINING - Vītola, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Based on the theoretical ideas of scholars in the field of dance, the article analyses the significance of correct breathing and its usage in movement performance in classical and modern dance acquisition.The most important condition for dancers is the daily workout, which develops an understanding of basic components of movements, one of the most significant being correct breathing. Application of correct breathing facilitates a comprehension among dancers of the possibilities of the body – the amplitude and quality of performed movements, as well as the ability to control the strength necessary for movement performance.This article aims to analyse the meaning of correct breathing and to justify its use among dancers acquiring classical and modern dance.The article makes use of the theoretical research method – characterising differences between classical and modern dance acquisition, analysing breathing and its correct usage during a dance performance.